2015
DOI: 10.1080/14783363.2015.1100517
|View full text |Cite
|
Sign up to set email alerts
|

Service quality perception and customer satisfaction in Islamic banks of Pakistan: the modified SERVQUAL model

Abstract: The aim of this study is to measure the relationship between service quality and customer satisfaction among the customers of Pakistani Islamic banks. This study employed a modified SERVQUAL model by introducing a unique dimension of compliance in the context of service industry. A self-administered questionnairebased field survey was conducted with the help of modified SERVQUAL dimensions. Data were gathered from 450 walk-in customers of Islamic bank. The sample data were statistically analysed through explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
257
5
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(295 citation statements)
references
References 72 publications
21
257
5
12
Order By: Relevance
“…The above rational emphasizes the exigency to gain service quality knowledge for Islamic banking to further concrete the phenomena along with associated concepts and issues. Thus this study focuses on the service quality knowledge and customer perception of Islamic bank customers which had been previously researched by (Faisal, Shabbir, Javed and Farooq, 2016;Ahmad, Rehman and Saif, 2010;Ali and Raza, 2015).…”
Section: Islamic Banking Sector (Bank Islam Brunei Darussalam (Bibd) mentioning
confidence: 99%
See 1 more Smart Citation
“…The above rational emphasizes the exigency to gain service quality knowledge for Islamic banking to further concrete the phenomena along with associated concepts and issues. Thus this study focuses on the service quality knowledge and customer perception of Islamic bank customers which had been previously researched by (Faisal, Shabbir, Javed and Farooq, 2016;Ahmad, Rehman and Saif, 2010;Ali and Raza, 2015).…”
Section: Islamic Banking Sector (Bank Islam Brunei Darussalam (Bibd) mentioning
confidence: 99%
“…The study suggested that demographic variables have different impact in the perception of service quality. Ali and Raza, (2015) measured service quality perception and customer satisfaction among Islamic bank customers in Pakistan adopting Carter model. The findings of the study suggested that all the dimensions of service quality have direct and positive relationship with customer satisfaction.…”
Section: Review Of Past Studiesmentioning
confidence: 99%
“…With little modifications in SERVQUAL due to contextual differences, it has been found valid in various services sectors. For example, educational institutes (Akhlaghi, Amini, & Akhlaghi, 2012), insurance companies (Tsoukatos & Rand, 2007), Travel agencies (Bigne´, Martı´nez, Miquel, & Andreu, 2003), Banks (Karatepe, Yavas, & Babakus, 2005), Islamic banks (Ali & Raza, 2017), hospitality industry (Akbaba, 2006), telecom (Johnson & Sirikit, 2002) etc. Although SERVQUAL is a recognized model and is highly applicable in services sector, it has been subject to criticism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been established many times that service quality is an important indicator of customer satisfaction (e.g. Ali & Raza, 2017, Namin, 2017 which ultimately leads to different stages of customer loyalty (Wahab, Hassan, Shahid, & Maon, 2016). The relationship is simple; the more loyal customer you have, the more profits for your organization (Ozantac, Saner, & Sen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in the investigations of intangibles, a predominance of sectors such as banking (Ali and Raza 2015;Ateba, Maredza, Ohei, Deka and Schutte 2015) and tourism (Pereira, Salgueiro and Rita 2016;Triantafillidou and Petala 2016) is manifested in this type of research. Specifically within the tourism sector, the research related to this theme varies from tourism modality, with research related to health tourism (Aziz, Md-Yusof, AbuBakar, Taib and Ayob 2015), sports (Hallmann, Mueller and Peters 2015), cultural (Chai, Bao, Sun and Cao 2015) but with a large predominance of mass tourism of sun and beach (Bujosa, Riera and Pons 2015).…”
Section: Introductionmentioning
confidence: 99%